Re-thinking the Way Cultural Value is Conceptualised for Cultural Music Festivals, Undertaken Through a Digital Approach: The Llangollen International Musical Eisteddfod - LEWIS THOMAS (2023)
The overarching purpose of this thesis is to provide an improved understanding of the ‘cultural values’ that are derived by the different visitor types attending the Llangollen International Musical Eisteddfod (LIME). Many academics have tried to measure the value of different elements of culture and the arts in monetary terms, yet not much work has been undertaken on how cultural values link to brand values. A different approach to conceptualising ‘cultural value’ is therefore proposed in this thesis, which examines the benefits of understanding value to be a co-constructed outcome of the visitor experience, which in itself mediated through the brand values communicated by the event. Following an extensive review of the literature, data were collected and analysed, with the aim of gaining an improved understanding of three main areas of interest. Firstly, the research presented in this thesis seeks to explore how cultural arts festivals can brand themselves in order to simultaneously attract visitors and communicate their core values. In this respect, the research presented in this thesis suggests that branding is more effective when the brand values used are consistent with the cultural values derived from the experience. Secondly, this thesis contributes to the understanding of value by identifying value typology that is appropriate to cultural arts festivals, using LIME as a critical example. Specifically, the research makes use of the typology to explain how values are understood in the overall experience. Thirdly, the research applied a digital approach to identify evidence of brand and cultural values being communicated through the use of user-generated-content posted on social media platforms. The findings suggest that digital media can aid the communication of both brand and cultural value to potential visitors. The reflections left by visitors on their experiences can result in meaningful values being communicated, which can be considered the ‘real value’ that the culture and the arts can have for people. The overall contribution of this thesis is to demonstrate the vital importance for the links between brand value and cultural value for an event to deliver authentic experiences, put across its core values and attract new audiences, while at the same time continuing to be commercially viable. The culture and the arts sector can reinforce their value proposition by providing more opportunities for visitors to give word-of-mouth, specifically around the benefits of the experience they receive, while at the same time being authentic to its brand values.